2016
DOI: 10.1016/j.drugpo.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

National population size estimation of illicit drug users through the network scale-up method in 2013 in Iran

Abstract: It seems that younger individuals and women are more desired to use new synthetic drugs such as crystal methamphetamine. Extending the preventive programs especially in youth as like as scaling up harm reduction services would be the main priorities in prevention and control of substance use in Iran. Because of poor service coverage and high stigma in women, more targeted programs in this affected population are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 19 publications
3
76
0
Order By: Relevance
“…Addiction among the youth has experienced an increasing trend. According to the Census 2005, 61.22 percent of addicts were between 20 and 29 years old (5). Alarmingly in the last two decades, the age of addicts and drug users has dropped below the age of 20 and in some cases even to 8 years old (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addiction among the youth has experienced an increasing trend. According to the Census 2005, 61.22 percent of addicts were between 20 and 29 years old (5). Alarmingly in the last two decades, the age of addicts and drug users has dropped below the age of 20 and in some cases even to 8 years old (6).…”
Section: Introductionmentioning
confidence: 99%
“…Statistics of Iran drug control headquarters show that in 2012, 2.65 percent of people in the 15 -64 year old age group use drugs. It also estimated the approximate number of addicts to be 1.325 million in Iran (4,5). Addiction among the youth has experienced an increasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…Another national study in 2013 used a network scale-up method in order to estimate the number of substance users (11). This study suggested that 440 000 (0.59%) people had used methamphetamine and 224 000 (0.3%) had used other types of synthetic drugs (amphetamine, ecstasy and LSD) at least once during the previous year.…”
Section: Prevalence Of Ats Use In the General Populationmentioning
confidence: 99%
“…However, in recent years, the illegal use of methamphetamine (MA) has become a new health problem (1). A recent study of 7535 people in 31 provinces indicated that after opioids, MA and hashish were the most frequently used illicit drugs (2). Among people who use opioids in Iran, MA use grew in popularity, from an estimated six percent in 2008 to 44% in 2012 (1).…”
Section: Introductionmentioning
confidence: 99%